Age effects on the acquisition of nominal and verbal inflections in an instructed setting - Pfenninger, Simone E. (Studies in Second Language Learning and Teaching, 2011)
This study examines evidence for the hypothesis (e.g., Muñoz, 2006) that an early starting age is not necessarily more beneficial to the successful learning of L2 inflectional morphology in strictly formal instructional settings. The present author investigated the quantitative and qualitative differences in the production and reception of 5 selected inflectional morphemes in English written performance and competence tasks by 100 early classroom learners and 100 late classroom learners of the same age. While an earlier age of first exposure and a longer instructional period was not associated with higher accuracy scores, the findings suggest distinct patterns in the productive and receptive knowledge abilities of inflectional morphology; the late classroom learners’ superiority seems to be rooted in their greater reliance upon memory-based item-by-item associative learning, as they are significantly stronger on tasks that might cause semantic difficulties, whereas the early classroom learners are marginally better on pattern-based processes for certain morphemes. This finding possibly supports Ullman’s (2005) proposal that, as procedural memory declines with age, older starters have difficulty in discovering regularities in the input and thus over-rely on the declarative memory system in L2 learning.